Straightness solution of the fully mechanized working face based on VR and DT technology - YAN Zewen; XIE Jiacheng; LI Suhua; SHEN Weidong; WANG Yirong; WANG Xuewen (Gong-kuang zidonghua, 2023)
The straightness problem is one of the neck problems in the intelligent construction of the fully mechanized working face. The key to solve this problem is to obtain the position and posture of the scraper conveyor or hydraulic support group. At present, most of the research on the straightness of fully mechanized working face is to discuss the straightness of hydraulic support and scraper conveyor separately. There are problems such as high cost and difficulty in implementation. In order to solve this problem, based on virtual reality(VR) and digital twin(DT) technology, the method to solve the straightness problem of the fully mechanized working face is explored. The hydraulic support, floating connection mechanism and scraper conveyor are considered as a whole system. The straightness solution framework of the fully mechanized working face is built. There are mainly five steps: mechanism analysis, model construction, fusion deduction, reconstruction monitoring and predictive control. It is pointed out that the key to the analysis of the relative position relationship of the fully mechanized supporting equipment is the floating connection mechanism connecting the hydraulic support base and the scraper conveyor. According to the motion characteristics of the floating connection mechanism, it is simplified into a robot model and solved by forward and reverse motion. According to the real coal seam environment, the motion simulation model of fully mechanized mining support equipment based on joints is established in Unity3D, and the VR scene is constructed to realize virtual and real mapping. Through non-contact visual sensor, virtual sensor, virtual-real fusion and other technologies, the information of sensor and point cloud are fused to perform the position and posture deduction of support equipment. Using the technology of virtual and reality interaction, combined with a real physical scenario, a DT system is constructed to achieve virtual monitoring of the fully mechanized working face. The travel distance required to ensure straightness is predicted in the virtual scene and fed back to the physical scene for straightness control.